2011
DOI: 10.1111/j.1745-4549.2011.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Processing on the Physicochemical Properties and Carotenoid Contents of Plantain Flour

Abstract: The effects of processing on the physicochemical properties as well as carotenoid contents of plantain flour were investigated. Unripe, semiripe and ripe plantain pulp were subjected to sun‐drying (50C, 72 h), boiled (100C, 15 min), roasted (120C, 10 min) and oven‐dried (60C, 20 min). The flour obtained was evaluated for their proximate composition, functional, pasting properties and sensory qualities. The result of proximate analysis showed that there were slight increase in moisture content, crude fiber, ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Total carotenoid was determined by the method described by Adegunwa et al [21]. 2 ml of distilled water was added to 5 g of plantain flour.…”
Section: Total Carotenoid Composition Of Plantain Floursmentioning
confidence: 99%
“…Total carotenoid was determined by the method described by Adegunwa et al [21]. 2 ml of distilled water was added to 5 g of plantain flour.…”
Section: Total Carotenoid Composition Of Plantain Floursmentioning
confidence: 99%
“…Carbohydrate has also been linked to influence water absorption capacity of foods [34]. This view was also supported by Adegunwa et al [30] who reported that observed differences in water absorption capacity of the carbohydrate based flours may be due to factors like their amylose/amylopectin ratio as well as their molecular structure.…”
Section: Functional Properties Of Flour Samplesmentioning
confidence: 66%
“…The water absorption capacity values of HQCF, DWSF, WREF and IPYF differs significantly (p<0.05) with values ranging from 120.79% to 229.41%. These variations in water absorption capacity values of the samples is an indication of the differences in the degree of engagement to form hydrogen and covalent bonds between starch chains as well as the degree of availability of water binding sites among the starches [29]; which might be due to various factors such as particle size, amylose/amylopectin ratio and molecular structure [30].…”
Section: Functional Properties Of Flour Samplesmentioning
confidence: 99%
“…The tannin was determined using the method of Adegunwa et al (26). About 0.5g of each sample was weighed and transferred into 50 ml distilled water and adequately mixed; the solution was left to stay at a temperature of 28°C for 30 minutes and filtered through No.…”
Section: Tannin Content Determinationmentioning
confidence: 99%